Intrahepatic Cholangiocarcinomas Have Histologically and Immunophenotypically Distinct Small and Large Duct Patterns. (October 2018) - Sigel, Carlie S.; Drill, Esther; Zhou, Yi; Basturk, Olca; Askan, Gokce; Pak, Linda M.; Vakiani, Efsevia; Wang, Tao; Boerner, Thomas; Do, Richard K.G.; Simpson, Amber L.; Jarnagin, William; et al.
Abstract : Intrahepatic cholangiocarcinomas are histologically heterogenous. Using a cohort of 184 clinically defined, resected intrahepatic cholangiocarcinomas, we retrospectively classified the histology into 4 subtypes: large duct (LD), small duct (SD) (predominantly tubular [SD1] or predominantly anastomosing/cholangiolar, [SD2]), or indeterminate. Then, we tested the 4 subtypes for associations with risk factors, patient outcomes, histology, and immunophenotypic characteristics. SD was the most common (84%; 24% SD1 and 60% SD2) with lower proportions of LD (8%), and indeterminate (8%). Primary sclerosing cholangitis was rare (2%), but correlated with LD ( P =0.005). Chronic hepatitis, frequent alcohol use, smoking, and steatosis had no histologic association. LD was associated with mucin production ( P <0.001), perineural invasion ( P =0.002), CA19-9 staining ( P <0.001), CK7 +, CK19 +, CD56 − immunophenotype ( P =0.005), and negative albumin RNA in situ hybridization ( P <0.001). SD was histologically nodular ( P =0.019), sclerotic ( P <0.001), hepatoid ( P =0.042), and infiltrative at the interface with hepatocytes ( P <0.001). Albumin was positive in 71% of SD and 18% of LD ( P =0.0021). Most albumin positive tumors (85%) lacked extracellular mucin ( P <0.001). S100P expression did not associate with subtype ( P >0.05). There was no difference in disease-specific or recurrence-free survival among the subtypes. Periductal infiltration and American Joint Committee on Cancer eighth edition pT stage predicted survival by multivariable analysis accounting for gross configuration, pT stage, and histologic type. pT2 had worse outcome relative to other pT stages. Significant differences in histology and albumin expression distinguish LD from SD, but there is insufficient evidence to support further subclassification of SD. Abstract : Supplemental Digital Content is available in the text.